2004
DOI: 10.1016/j.femsle.2004.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous complementation of the exopolysaccharide synthesis and carbon utilization phenotypes ofSinorhizobium melilotiRm1021 polyhydroxyalkanoate synthesis mutants

Abstract: A reduced exopolysaccharide phenotype is associated with inability to synthesize polyhydroxyalkanaote (PHA) stores in Sinorhizobium meliloti strain Rm1021. Loss of function mutations in phbB and phbC result in non-mucoid colony morphology on Yeast Mannitol Agar, compared to the mucoid phenotype exhibited by the parental strain. This phenotype is attributed to reduction in succinoglycan synthesis. We have used complementation of this phenotype and the previously described D-3-hydroxybutyrate/acetoacetate utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
2
32
0
1
Order By: Relevance
“…Since the double mutant produced a significantly larger amount of glycogen than that produced by the phbC mutant in YMB medium (Table 2), we assume that the inclusion in the double mutant could be glycogen. However, the carbon flow, especially a correlation between PHB and glycogen in rhizobia, is far from clear (1,9,27,38,39). We are pursuing further studies to clarify the role of phasins in regulating storage polymer synthesis and carbon metabolism in S. meliloti.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the double mutant produced a significantly larger amount of glycogen than that produced by the phbC mutant in YMB medium (Table 2), we assume that the inclusion in the double mutant could be glycogen. However, the carbon flow, especially a correlation between PHB and glycogen in rhizobia, is far from clear (1,9,27,38,39). We are pursuing further studies to clarify the role of phasins in regulating storage polymer synthesis and carbon metabolism in S. meliloti.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing result was the increase in EPS synthesis in the phaP mutants under growth conditions that yield reduced levels of EPS synthesis in other PHB synthesis mutants (1). Whether this increased EPS is succinoglycan, galactoglucan, or some other EPS is not known at this point.…”
Section: Discussionmentioning
confidence: 99%
“…39) phbB mutants have also been reported for poor growth and less PHB accumulation in many bacteria, suggesting its usefulness during PHB synthesis process. 40) Additionally, many previous studies have amplified phbB gene in the isolates to deduce the molecular nature of PHB production in them. 41,42) Thus, in order to confirm the role of phbB gene of phb operon during pathway of PHB synthesis, amplification of phbB gene was carried out in the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent proteomic and transcriptomic studies have indicated that both phaC1 and phaC2 are present in nodule bacteroids (13,14). In a different study, Aneja and coworkers attempted to complement a phaC-defective Ensifer (formerly Sinorhizobium) meliloti mutant with a B. japonicum cosmid library in order to isolate genes encoding functional PHA synthases in this rhizobial species and were successful only with phaC1 (15).…”
mentioning
confidence: 99%